Co-degradation of phenol and m-cresol by upflow anaerobic sludge blanket reactor - Farooqi, I.H. (2007)
The study was performed to assess the efficacy of an upflow anaerobic sludge blanket reactor for the degradation of mixtures of phenol and m-cresol. The experiments were performed in an upflow anaerobic sludge blanket reactor. The reactor was seeded with digested sewage sludge and was initially operated at 24 HRT. A phenol concentration of 200mg/L was fed to the reactor to acclimatize the microorganisms to phenols. Subsequently the dosages of phenols were increased to 400mg/L, 500mg/L, and 600mg/L. Cresols were introduced in the reactor when phenol removal efficiency of 77% was achieved at phenol concentration of 600mg/L. Different phenol to m-cresol ratios were tried and the performance of the reactor was evaluated for each case. The result demonstrates that it is important to consider phenol/ m-cresol ratio to avoid toxic effects and both can be co-degraded successfully under anaerobic conditions provided proper acclimatization time is given.